CASE REPORT A Double Thoracodorsal Artery Perforator Flap Technique for the Treatment of Pectus Excavatum - Sinna, Raphaël (Open Science Company, LLC, 2010)
Background: Pectus excavatum is a common congenital deformity involving the anterior thoracic wall. It can be treated with several surgical approaches. Material and methods: To our best of knowledge, this is the first case of pectus excavatum repair via a 2-stage double thoracodorsal artery perforator flap procedure in a 37-year-old patient. Results: We obtained a satisfactory result in which the missing volume was correctly replaced in the absence of dorsal sequelae. The patient was very satisfied despite the dorsal scars. Conclusion: This new approach broadens the surgeon's options for the correction of thoracic deformities.